Evaluasi Imunogenisitas Protein Pili 65,5 kDa Klebsiella Pneumoniae terhadap Kadar IL1β Serum Mencit BALB/c - Aqilla Sakanti Chandrarini (Fakultas Kedokteran, 2025)
Klebsiella pneumoniae (K. pneumoniae) is a Gram-negative bacterium that causes pneumonia with high morbidity and mortality worldwide. Rising resistance to βlactams and carbapenems has led to multidrug-resistant K. pneumoniae (MDRKP), underscoring the need for non-antibiotic preventive strategies such as subunit vaccines. The 65.5 kDa pili protein has been reported to be immunogenic and may serve as a vaccine antigen. This study aimed to evaluate its immunogenicity by assessing serum Interleukin-1β (IL-1β) levels in BALB/c mice. Mice were divided into three groups: control (K1), adjuvant (K2), and treatment (K3). The treatment group received the 65.5 kDa pili protein, and serum IL-1β levels were measured by ELISA. Statistical analysis included Shapiro-Wilk, Levene, One Way ANOVA, and Post Hoc tests. The treatment group showed a significant increase in IL-1β compared to control and adjuvant groups (p=0.000). The adjuvant group also showed higher IL-1β than controls (p=0.041), indicating its stimulatory role. Mechanistically, pili proteins act as pathogen-associated molecular patterns (PAMPs), activating Toll-like receptors, NF-κB signaling, and NLRP3 inflammasome pathways to enhance IL-1β secretion. The combination of pili protein with adjuvant demonstrated synergistic effects, producing stronger innate immune responses and facilitating the transition to adaptive immunity. In conclusion, the 65.5 kDa pili protein of K. pneumoniae demonstrated significant immunogenicity through increased IL-1β production in BALB/c mice. These results support its potential as a subunit vaccine candidate against K. pneumoniae, offering an alternative preventive approach amid growing antibiotic resistance.
Entry oleh Arif 2026 Maret 26
Keywords: Klebsiella pneumoniae; IL-1β; immunogenicity; Subunit vaccine; 65.5 kDa pili protein